Biologized Technologies for Cultivation of Field Crops in the Organic Farming System of West Kazakhstan - Nasiyev, B. N.; Bekkaliyeva, A. K.; Vassilina, T. K.; Shibaikin, V. A.; Zhylkybay, A. M. (JOURNAL OF ECOLOGICAL ENGINEERING, 2022)
n studies aimed at expanding the range of the organic farming system, the authors studied the comparative productivity of such field crops like barley and safflower cultivated with the use of traditional and biologized technologies. The use of biological preparations and organic biofertffizers of the latest generation was studied as a biologized technology on barley and safflower crops. As shown by the experimental data, with the biologized technology in the conditions of the zone in question. the yield of barley increased by 27.02% compared to traditional technologies, the harvest of protein increased by 0.02 t/ha, and the energy value by 2.25 GJ/ha. In this work, it was concluded that the use of the biologized technology of barley and safflower cultivation was important to improve the efficiency of agricultural landscape management in the system of organic fanning, which constitutes the scientific novelty of the study. В исследованиях, направленных на расширение ассортимента системы органического земледелия, авторы изучали сравнительную продуктивность таких полевых культур, как ячмень и сафлор, возделываемых по традиционной и биологизированной технологиям. Применение биопрепаратов и органических биоудобрений последнего поколения изучено в качестве биологизированной технологии на посевах ячменя и сафлора. Как показали опытные данные, при биологизированной технологии в условиях рассматриваемой зоны. урожайность ячменя увеличилась на 27,02% по сравнению с традиционными технологиями, сбор белка увеличился на 0,02 т/га, энергетическая ценность на 2,25 ГДж/га. В работе сделан вывод о важности использования биологизированной технологии возделывания ячменя и сафлора для повышения эффективности управления агроландшафтом в системе органического веерования, что и составляет научную новизну исследования.
Keywords: импакт-фактор 2022; web of sciense; кларивате аналитикс; дальнее зарубежье; научный журнал; периодическое издание; зерновые культуры; сафлор; зко; ячмень; масличные культуры; агроландшафт